2011
DOI: 10.1055/s-0031-1291295
|View full text |Cite
|
Sign up to set email alerts
|

Does Pain Improve Earlier than Mood in Depressed Patients with Painful Physical Symptoms Treated with Duloxetine?

Abstract: In duloxetine-responders to both pain and mood, self-rated pain improved slightly earlier than self-rated mood. The short temporal dissociation between pain and mood improvement might be explained by an earlier conscious perception of pain than mood changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 26 publications
1
4
0
1
Order By: Relevance
“…Fava et al [19] argue that 50 % of the improvement in pain severity with the use of duloxetine was independent of the amelioration of depressive symptoms. In those of their depressed patients who responded to duloxetine, a self-rated pain reduction of > 50 % was observed slightly earlier (mean 6.3 days) than the self-rated time to 50 % mood response (7.6 days), suggesting earlier conscious perception of pain than of mood changes [36]. The results of our study seem to confirm this assumption; however, the reasons for this phenomenon have not been thoroughly explained.…”
Section: Discussionsupporting
confidence: 56%
“…Fava et al [19] argue that 50 % of the improvement in pain severity with the use of duloxetine was independent of the amelioration of depressive symptoms. In those of their depressed patients who responded to duloxetine, a self-rated pain reduction of > 50 % was observed slightly earlier (mean 6.3 days) than the self-rated time to 50 % mood response (7.6 days), suggesting earlier conscious perception of pain than of mood changes [36]. The results of our study seem to confirm this assumption; however, the reasons for this phenomenon have not been thoroughly explained.…”
Section: Discussionsupporting
confidence: 56%
“…It remains uncertain whether the apparent analgesic effects of 5-HT-modulating drugs are a direct consequence of increased availability of 5-HT or as a secondary effect of mood changes. Current arguments favour the direct effects of 5-HT, as analgesia generally occurs prior to any changes in mood (Hegerl et al 2012 ; McQuay et al 1996 ). A technique to experimentally investigate the action of 5-HT in humans is via global depletion of its precursor tryptophan (TRP) using a method known as acute TRP depletion (ATD).…”
Section: Introductionmentioning
confidence: 99%
“…Whilst there is still debate on the involvement of mood changes induced by the ATD (Benkelfat et al 1994 ; Delgado et al 1990 ; Ellenbogen et al 1999 ; Robinson and Sahakian 2009 ), studies have successfully dissociated pain and mood changes following serotonin and noradrenaline supplementation in patients suffering from depression (Hegerl et al 2012 ). A large-scale meta-analysis of 5-HT depletion studies has shown that mood is not affected within a healthy volunteer cohort with no history of depression (Young 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Fava et al (2004) [14] argue that 50% of the improvement in pain severity with the use of this drug was independent of the amelioration of depressive symptoms. In depressed patients who responded to duloxetine, self-rated pain reduction of N 50% was observed slightly earlier (mean 6.3 days) than self-rated time to 50% mood response (7.6 days), suggesting earlier conscious perception of pain than mood changes [26]. The results of our study suggest that 50% reduction of pain was obtained during the first 2 weeks of treatment with escitalopram and nortriptyline, whereas a 50% alleviation of severity of depression was only attained later.…”
Section: Discussionmentioning
confidence: 85%